Vibration and Acoustic Analysis of a Refrigerator Cabinet Base Plate - Deveci, Can Deniz; Yardımoğlu, Bülent (Izmir Institute of Technology, 2013)
This research study deals with the vibration and acoustics analysis of a refrigerator cabinet base plate by using Theoretical Modal Analysis by Finite Element Method and Experimental Modal Analysis. In this study, a cabinet base plate is considered to investigate the titled problem. This cabinet base plate has several non-uniform geometrical properties such as holes, stiffeners and mounting places. Due to the aforementioned non-uniformity, numerical methods are used to find the vibration and acoustics properties such components. The aim of the first important part of this thesis is to provide the theoretical background to the readers. Other parts of this thesis are presented for theoretical modal analysis of cabinet base plate which is carried out by using solid element in ABAQUS and experimental modal analysis that is accomplished by using dB4-1 Mobil Analyser and its connections. The modal parameters found from both numerical and experimental methods are compared and good agreement is found. After determining the agreement, the proper modification has been done for the system which generates undesired sound due to the natural frequency.
Thesis (Master)--Izmir Institute of Technology, Mechanical Engineering, Izmir, 2013
Includes bibliographical references (leaves: 26)
Text in English; Abstract: Turkish and English
x, 26 leaves
Keywords: Vibration--Mathematical models; Refrigerators; Acoustic emission testing